Characterization of OXA232-Producing Carbapenem-Resistant Klebsiella pneumoniae: Genomic Analysis and Virulence Assessment - Li Zhouxun; Wu Chunyan; Cai Xuemei; Song Yongli; Zheng Xingping; He Yuan; Song Guibo (Polish Journal of Microbiology)
Globally, the infection rate of carbapenem-resistant Klebsiella pneumoniae (CRKP) producing OXA-48-like carbapenemase is increasing, posing a significant public health threat due to its high antibiotic resistance. Between December 2019 and April 2023, ten CRKP strains carrying the OXA-48-like carbapenemase were isolated from inpatients at the First Affiliated Hospital of Kunming Medical University. Wholegenome sequencing (WGS) revealed that all strains carried the OXA-232 gene, a variant of OXA-48-like, located on the non-conjugative ColKP3 plasmid. Sequence typing identified nine strains as ST231 and one as ST11. The ST231 strains carried common virulence genes, including yersiniabactin (ybtA, fyuA, irp2) and aerobactin (iucABCD, iutA), while the ST11 strain carried high-virulence genes (rmpA, rmpA2, peg-344) as well as KPC-2 and OXA-232 carbapenemase genes on separate plasmids, suggesting that CRKP can harbor multiple plasmids with carbapenemase genes. Sequence typing of 264 global ST231 CRKP isolates (n = 264) showed a distinct clonal relationship between our strains and Indian CRKP isolates, indicating potential cross-border transmission. The virulence potential and immune response of the ST231 strains were assessed using a mouse respiratory infection model. The concentrations of inflammatory factors CCL2/MCP-1, IL-6, and TNF-α in the alveolar lavage fluid and blood of the model mice were detected. Combined with the pathological analysis of lung and liver tissues, it reveals variability in virulence and immune response despite carrying identical resistance and virulence genes. This underscores the urgent need for monitoring and tailored public health strategies to combat the global spread of drug-resistant strains.